Psychodata: disassembling the psychological, economic, and statistical infrastructure of 'social-emotional learning' - Williamson, Ben (Journal of education policy, 2021)
Psychology and economics are powerful sources of expert knowledge in contemporary governance. Social and emotional learning (SEL) is becoming a priority in education policy in many parts of the world. Based on the enumeration of students' 'noncognitive' skills, SEL consists of a 'psycho-economic' combination of psychometrics with economic analysis, and is producing novel forms of statistical 'psychodata' about students. Constituted by an expanding infrastructure of technologies, metrics, people, money and policies, SEL has travelled transnationally through the advocacy of psychologists, economists, and behavioural scientists, with support from think tank coalitions, philanthropies, software companies, investment schemes, and international organizations. The article examines the emerging SEL infrastructure, identifying how psychological and economics experts are producing policy-relevant scientific knowledge and statistical psychodata to influence the direction of SEL policies. It examines how the OECD Study on Social and Emotional Skills, a large-scale computer-based assessment, makes 'personality' an international focus for policy intervention and 'human capital' formation, thereby translating measurable socio-emotional indicators into predicted socio-economic outcomes. The SEL measurement infrastructure instantiates psychological governance within education, one underpinned by a political rationality in which society is measured effectively through scientific fact-finding and subjects are managed affectively through psychological intervention.